\(x=\sqrt{2+\sqrt{3}}\)

        \(y=\sqrt{6-3\sqrt{3}}\)

K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

28 tháng 1 2020

\(a,x=\sqrt{27}-\sqrt{2}\)\(=3\sqrt{3}-\sqrt{2}>3\sqrt{3}-\sqrt{3}=2\sqrt{3}\)

Mà: \(y=\sqrt{3}< 2\sqrt{3}\)

\(\Rightarrow x>y\)

\(b,x=\sqrt{5\sqrt{6}}\Rightarrow x^4=5^2.6=150\)

\(y=\sqrt{6\sqrt{5}}\Rightarrow y^4=6^2.5=180\)

\(\Rightarrow x^4< y^4\Rightarrow x< y\left(x,y>0\right)\)

\(c,x=2m;y=m+2\)

Ta có: \(x-y=2m-\left(m+2\right)=m-2\)

Ta xét các trường hợp:

  • Nếu \(m< 2\Rightarrow m-2< 0\Rightarrow x< y\)
  • Nếu \(m=2\Rightarrow m-2=0\Rightarrow x=y\)
  • Nếu \(m>2\Rightarrow m-2=0\Rightarrow x>y\)
27 tháng 1 2017

CÂU 3 : ĐỀ BÀI , SUY RA :

X-1 + X-2 =3 <=> 2X = 6 <=> X =3 

14 tháng 10 2018

Q= [\(\frac{\left(\sqrt{x}-\sqrt{y}\right)\left(\sqrt{x}+\sqrt{y}\right)}{\sqrt{x}-\sqrt{y}}+\frac{\left(\sqrt{x}-\sqrt{y}\right)\left(x+\sqrt{xy}+y\right)}{\left(\sqrt{y}-\sqrt{x}\right)\left(\sqrt{y}+\sqrt{x}\right)}\)]\(:\frac{x-2\sqrt{xy}+y+\sqrt{xy}}{\sqrt{x}+\sqrt{y}}\)

\(Q=\left(\sqrt{x}+\sqrt{y}-\frac{x+\sqrt{xy}+y}{\sqrt{x}+\sqrt{y}}\right):\frac{x-\sqrt{xy}+y}{\sqrt{x}+\sqrt{y}}\)

\(Q=\frac{x+2\sqrt{xy}+y-x-\sqrt{xy}-y}{\sqrt{x}+\sqrt{y}}.\frac{\sqrt{x}+\sqrt{y}}{x-\sqrt{xy}+y}\)

\(Q=\frac{\sqrt{xy}}{x-\sqrt{xy}+y}\)

15 tháng 10 2018

phan 3 nua